2021
DOI: 10.3389/fnut.2021.756413
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Children and Young Adults With Type 2 Diabetes: A Narrative Review With Emphasis on the Potential of Intermittent Fasting as a Preventive Strategy

Abstract: Background: The world is still struggling to control the COVID-19 pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The level of uncertainty regarding the virus is still significantly high. The virus behaves differently in children and young adults. Most children and adolescents are either asymptomatic or have mild symptoms. They generally have a very good prognosis. However, it is not well-known whether children and young adults with type 2 diabetes are at risk of getting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 153 publications
(196 reference statements)
0
8
0
Order By: Relevance
“…Although adolescents practice Ramadan fasting and other forms of intermittent fasting, the impact of such fasting on glucose biomarkers in this age group has not been adequately studied 108 . However, it has been hypothesized that adolescents with T2D will probably benefit from intermittent fasting similar to adults, given a similar pathogenesis of the disease 108 .…”
Section: Fasting In Young People With T2dmentioning
confidence: 99%
See 3 more Smart Citations
“…Although adolescents practice Ramadan fasting and other forms of intermittent fasting, the impact of such fasting on glucose biomarkers in this age group has not been adequately studied 108 . However, it has been hypothesized that adolescents with T2D will probably benefit from intermittent fasting similar to adults, given a similar pathogenesis of the disease 108 .…”
Section: Fasting In Young People With T2dmentioning
confidence: 99%
“…118 Although adolescents practice Ramadan fasting and other forms of intermittent fasting, the impact of such fasting on glucose biomarkers in this age group has not been adequately studied. 108 However, it has been hypothesized that adolescents with T2D will probably benefit from intermittent fasting similar to adults, given a similar pathogenesis of the disease. 108 Several studies reported that intensive education programs before and during Ramadan could significantly improve and prevent the complications of diabetes such as hypoglycemia.…”
Section: Fasting In Young People With T2dmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies in 2021 continued to address the interplay between diabetes and COVID-19. Elmajnoun et al 39 summarized the impacts of the COVID-19 pandemic on children and young adults with T2DM and identified the knowledge gaps in the literature. They also explored the potential of intermittent fasting in reversing the pathogenesis of diabetes and highlighted how this approach could prevent these patients from developing chronic complications.…”
Section: Covid-19 and Ramadanmentioning
confidence: 99%